RME-BASED DOODLE ART COMICS TO STRENGTHEN ELEMENTARY STUDENTS’ NUMERACY LITERACY - Rahmi Hayati; Edi Syahputra; Edy Surya; M. Rezeki Muamar; Fazrina Saumi (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Numeracy literacy is an essential competency that should be developed from the elementary school level to help students understand and apply mathematical concepts in daily life. However, elementary school students’ numeracy literacy remains low, especially in understanding problems, connecting numerical information, and solving contextual mathematical tasks. This condition is caused by mathematics learning that is still abstract, procedural, and less connected to students’ real-life experiences. Therefore, contextual and engaging learning media are needed to support numeracy learning. This study aims to develop a Doodle Art comic based on Realistic Mathematics Education (RME) to enhance elementary school students’ numeracy literacy. The study employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The research instruments included validation sheets, teacher and student questionnaires, numeracy literacy tests, observations, and interviews. The results showed that the RME-based Doodle Art comic was categorized as highly feasible, with an average validation score of 4.41. Teacher responses obtained an average score of 4.54, categorized as very practical, while student responses obtained an average score of 4.50, categorized as very good. In addition, students’ numeracy literacy scores increased from 61.10 in the pretest to 76.18 in the posttest. The study concludes that the RME-based Doodle Art comic has the potential to become an innovative and contextual learning medium for improving elementary school students’ numeracy literacy.